Trajectory of change in brain complement factors from neonatal to young adult humans. Issue 3 (15th December 2020) - Sager, Rachel E. H.; Walker, Adam K.; Middleton, Frank; Robinson, Kate; Webster, Maree J.; Weickert, Cynthia Shannon
Abstract: Immune system components also regulate synapse formation and refinement in neurodevelopment. The complement pathway, associated with cell lysis and phagocytosis, is implicated in synaptic elimination. Aberrant adolescent synaptic pruning may underpin schizophrenia onset; thus, changes in cortical complement activity during human development are of major interest. Complement is genetically linked to schizophrenia via increased C4 copy number variants, but the developmental trajectory of complement expression in the human brain is undetermined. As complement increases during periods of active synaptic engulfment in rodents, we hypothesized that complement expression would increase during postnatal development in humans, particularly during adolescence. Using human postmortem prefrontal cortex, we observed that complement activator (C1QB and C3) transcripts peaked in early neurodevelopment, and were highest in toddlers, declining in teenagers (all ANCOVAs between F  = 2.41 –3.325, p  = .01–0.05). We found that C4 protein was higher at 1–5 years ( H  = 16.378, p  = .012), whereas C3 protein levels were unchanged with age. The microglial complement receptor subunit CD11b increased in mRNA early in life and peaked in the toddler brain (ANCOVA: pH, F  = 4.186, p  = .003). Complement inhibitors (CD46 and CD55) increased at school age, but failed to decrease like complement activators (both ANCOVAs, F  > 4.4, p  < .01). These data suggest the activation of complement in the human prefrontal cortex occurs between 1 and 5 years. We did not find evidence of induction of complement factors during adolescence and instead found increased or sustained levels of complement inhibitor mRNA at maturation. Dysregulation of these typical patterns of complement may predispose the brain to neurodevelopmental disorders such as autism or schizophrenia. Abstract : In the prefrontal cortex, we found that classical complement components (purple line) increased over the first 5 years of human life, similar to previously reported growth of dendritic spines and pre‐synaptic proteins (lines represent averages). Elements of classical complement pathway then decreased over the subsequent 20 years. It is less clear to what extent or at what rate dendritic spines and synaptic densities may decrease after age 5, due to the small number of brains studied (dotted lines) in prevous publications. Age is plotted on a log scale early in life when brain growth is exponential, then on a linear scale when brain growth attenuates. Supplemental materials include additional information regarding the calculations used in the construction of this graph.